Estudo da influência da adição de serragem de couro tratada quimicamente nas características de argamassas de cimento Portland - Shih, Yung Yuan (2009)
The purpose of this study was to examine the major environmental concern for the large volume of toxic wastes generated by industries of tanneries and the search for a technological solution for the treatment of this waste. The attempt to tie the chromium ion present on residue, shave chrome leather, was used in three steps. In the first step, solutions were prepared with different pHs (acidic, neutral, and basic) and concentrations of residue, obtaining the solution called waste treated . In the second stage, cement pastes were obtained by mixture of the cement Portland, water, and addition of different proportions of waste treated (5 and 10% on the mass of cement). Normal test of consistency, workability, and the set time were applied on these pastes in its fresh state. Also, the pHs of the paste were evaluated to verify the influence of it on setting time. Finally, in the third stage, samples were prepared using mortar and after 28 days were physically characterized and tested for axial compressive strength. The most promising compositions were subjected for the structural characterization for analysis of the phases formed (DRX) and the microstructure (MEV / EDS). The results show that the reagents used for the pre-treatment of the residue are effective, but it causes some decrease of the mechanical strength of the mortar. The pHs of the waste treated do not modify that much on characteristic of the paste and mortar on the fresh and hardened state. It is expected that these results will contribute a solution to an environmental problem of a very important sector for Brazilian companies, which is industries of tannery for the production of leather.